Associations between Thematic Content and Memory Detail in Trauma Narratives. Issue 4 (2nd April 2013) - Welton‐Mitchell, Courtney; McIntosh, Daniel N.; DePrince, Anne P.
Summary This study examined whether thematic content (e.g., fear, anger, alienation, self‐blame, and spirituality) in trauma narratives predicted memory detail. Trauma‐specific memory models suggest that trauma narrative themes are associated with much sensory detail; general autobiographical memory models suggest that themes are associated with little context detail. Seventy‐one narratives from a diverse community sample exposed to a variety of traumatic events (e.g., sexual assault, natural disasters) were coded for themes and detail. Analyses controlled for narrative length, childhood or adulthood occurrence, self‐reported post‐traumatic stress disorder, depression and dissociation symptoms. Fear themes were associated with greater sensory detail; anger and spirituality themes were associated with less context detail. Findings support a link between thematic content and detail, and may partially explain why details in memory for traumatic events sometimes appear better and other times worse than memory for other events. Memory models may benefit from specification based on themes in trauma narratives. Copyright © 2013 John Wiley & Sons, Ltd.